2011
DOI: 10.1111/j.1365-3156.2011.02844.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rotavirus vaccination on diarrhoea mortality and hospital admissions in Brazil

Abstract: Summaryobjective To analyse the data reported by the national surveillance system of Brazil, including data on diarrhoea mortality and hospital admissions before and after rotavirus vaccine introduction, and evaluate the impact of its widespread use under operational conditions. methodRetrospective analysis of routinely collected data was reported by several surveillance systems of Brazil, comprising an 8-year period of all diarrhoea-related hospitalisations and deaths in children <5 years old (2002)(2003)(200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 21 publications
3
20
0
4
Order By: Relevance
“…Similarly, the decrease in the mortality rate due to gastroenteritis was greater than the decrease in hospitalization rates (47% and 20%, respectively. This result was also in agreement with the fi ndings in the literature (10) (25) . An important reduction in admissions caused by gastroenteritis in children occurred in Europe, even in countries with low immunization coverage, for instance (30) .…”
Section: Methods Of Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, the decrease in the mortality rate due to gastroenteritis was greater than the decrease in hospitalization rates (47% and 20%, respectively. This result was also in agreement with the fi ndings in the literature (10) (25) . An important reduction in admissions caused by gastroenteritis in children occurred in Europe, even in countries with low immunization coverage, for instance (30) .…”
Section: Methods Of Analysissupporting
confidence: 93%
“…These data were similar to the fi ndings of other studies that showed reductions varying from 17 to 48% (21) (22) (23) (25) . Similarly, the decrease in the mortality rate due to gastroenteritis was greater than the decrease in hospitalization rates (47% and 20%, respectively.…”
Section: Methods Of Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Impact studies conducted in Brazil using data from the Datasus have shown a reduction of hospital admissions due to acute diarrhea in children less than 5 years of age. In Brazil, the reduction ranged from 17 to 21.4%; 12,20 in the South and Southeast region, the reduction was 35% in the year 2007; 21 in the Southeast region the reduction was 21%; 12 and in the State of São Paulo the reduction ranged from 21 to 40%. 13,22 In the peak period of rotavirus infection (May and June), the reduction in hospital admissions due to acute diarrhea after the introduction of the vaccine was 82%, suggesting that the effectiveness of the vaccine was good.…”
Section: Discussionmentioning
confidence: 96%
“…Isto ocorreu também na implantação da vacina de rotavirus, quando houve uma diminuição dos casos de diarreia anterior ao início da imunização 10 . Além disso, a redução de mortalidade por diarreia foi diferente em diferentes regiões, sendo maior nas regiões mais pobres do país 11 .…”
Section: Jornal De Pediatriaunclassified